1971
DOI: 10.1111/j.1365-2494.1971.tb00639.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrogen, Stocking Rate and Frequency of Grazing by Beef Cattle on the Output of Pasture

Abstract: Two successive grazing experiments were conducted over 12 weeks on perennial ryegrass pastures with 50 and 44 young cattle to study the effect of N fertilizer when applied at a daily rate of 1 or 3 kg N/ha. At each level of N two stocking rates differing hy 20% were imposed. At the liigher N level and stocking rate, three frequencies of grazing were imposed.At the stocking rates imposed N tended to reduce the daily liveweight gain per head, hut increased the total liveweight gain per ha hy from 0-79 to 1-58 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

1972
1972
1984
1984

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…The results in Table 4 show that in the first 12 weeks of each season there was a response of about 1-3 kg gain/kg N, declining to 1-14 and 0-96, respectively, for the 20-week periods of 1970 and 1971. The corresponding values for ME ranged from 27 to 20 Mcal/kg N and in terms of DM from 10-4 to 7-7 kg/kg N. These values are slightly higher than those reported by Escuder et ai (8), but in terms of DM they are about 10% lower than those reported by Reid (15) in cutting experiments over the same range of fertilizer N. In terms of liveweight gain/kg N they exceed the values reported by Tayler (6) and Escuder et al (8), but are similar to those reported by Browne (4,5). They suggest that a response of at least 1 kg gain/kg N applied can be expected from N applications up to 300 kg/ha.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The results in Table 4 show that in the first 12 weeks of each season there was a response of about 1-3 kg gain/kg N, declining to 1-14 and 0-96, respectively, for the 20-week periods of 1970 and 1971. The corresponding values for ME ranged from 27 to 20 Mcal/kg N and in terms of DM from 10-4 to 7-7 kg/kg N. These values are slightly higher than those reported by Escuder et ai (8), but in terms of DM they are about 10% lower than those reported by Reid (15) in cutting experiments over the same range of fertilizer N. In terms of liveweight gain/kg N they exceed the values reported by Tayler (6) and Escuder et al (8), but are similar to those reported by Browne (4,5). They suggest that a response of at least 1 kg gain/kg N applied can be expected from N applications up to 300 kg/ha.…”
Section: Discussioncontrasting
confidence: 59%
“…They are shown for the first 12 weeks in each year, to facilitate comparison with Escuder et al (8), and also for the full 20-week experimental period. In each year further grazing amounted to 100-200 grazing days and 1000-2000 Meal, ME/ha were obtained in the late autumn grazing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The smaller liveweight gains made by the bullocks in the last third of the grazing season (Fig. 1) is a feature also noted by Browne and Walshe (8), Escuder et al (11), and Yiakoumettis and Holmes (22). This efFect could be due to a combination of declining digestibihty, increased faecal contami- nation of herbage and change in body condition of the animals.…”
Section: Botanical Composition Of the Swardmentioning
confidence: 73%